“Desarrollo de una aplicación web y móvil para el control de inventario de productos y de activos en el Veci Supermercado, ubicado en el sector de San Felipe cantón Latacunga. “ - Maisincho Chiliquinga, Jostin Elian (2024)
The present research focuses on the development of a web and mobile application to optimize inventory management of products and assets at Veci Supermarket, a retail business committed to operational excellence. Inspired by successful cases such as supermarket chains at a national level, the agile Scrum methodology will be employed to ensure effective collaboration between the development team and the project beneficiaries. Free licensing software development tools such as Php and Android Studio will be used. The IEEE standard was utilized for requirements gathering, enabling the analysis of client needs for system development. The application will offer key features such as real-time inventory management and fixed asset control, enhancing not only the supermarket's operational efficiency but also enriching the customer experience by providing access to product information. This project signifies a significant technological shift for Veci Supermarket, which previously relied on manual inventory management methods and outdated systems with no benefits. The introduction of the web and mobile application will enable the company to abandon obsolete processes and adopt a modern and efficient solution. In summary, the development of this application represents a crucial step towards the modernization and sustained competitiveness of Veci Supermarket in the retail market.